'Sadly I think we are sort of still quite white, middle-class really' – Inequities in access to bereavement support: Findings from a mixed methods study. (April 2023) - Selman, Lucy E; Sutton, Eileen; Medeiros Mirra, Renata; Stone, Tracey; Gilbert, Emma; Rolston, Yansie; Murray, Karl; Longo, Mirella; Seddon, Kathy; Penny, Alison; Mayland, Catriona R; Wakefield, Donna; et al.
Background: Voluntary and community sector bereavement services are central to bereavement support in the UK. Aim: To determine service providers' perspectives on access to their support before and during the COVID-19 pandemic. Design: Mixed methods study using an explanatory sequential design: (1) Cross-sectional online survey of UK bereavement services; (2) Qualitative interviews with staff and volunteers at selected services. Settings/participants: 147 services participated in the survey; 24 interviews were conducted across 14 services. Results: 67.3% of services reported there were groups with unmet needs not accessing their services before the pandemic; most frequently people from minoritised ethnic communities (49%), sexual minority groups (26.5%), deprived areas (24.5%) and men (23.8%). Compared with before the pandemic, 3.4% of services were seeing more people from minoritised ethnic groups, while 6.1% were seeing fewer. 25.2% of services did not collect ethnicity data. Qualitative findings demonstrated the disproportionate impact of the pandemic on minoritised ethnic communities, including disruption to care/mourning practices, and the need for culturally appropriate support. During the pandemic outreach activities were sometimes deprioritised; however, increased collaboration was also reported. Online provision improved access but excluded some. Positive interventions to increase equity included collecting client demographic data; improving outreach, language accessibility and staff representation; supporting other professionals to provide bereavement support; local collaboration and co-production. Conclusions: Service providers report inequities in access to bereavement support. Attention needs to be paid to identifying, assessing and meeting unmet needs for appropriate bereavement support. Identified positive interventions can inform service provision and research.